Educator‐Reported Instructional Characteristics of Grade 1 Reading Interventions within a CBM Assessment System. Issue 2 (21st January 2019) - Nese, Joseph F. T.; Farley, Dan; Anderson, Daniel
Abstract: We used data from the 2014–2015 easyCBM assessment system to explore the applied reading intervention characteristics in a sample of 3, 074 Grade 1 students (and 5, 145 interventions) in school districts applying a multitiered systems of support (MTSS) framework. We describe the number of interventions, number of assessments, the intervention start dates, curricula, instructional strategies, tier, group size, frequency, dosage, total time, and quantitative intensity. We found variance across all instructional variables, with 156 curricula and 59 instructional strategies applied. Based on our data, a "typical" intervention was a Tier 2 intervention that began before October, was delivered for 30 minutes/day for 5 days/week in a group with three to five students, was changed once if at all, and student progress was most likely monitored with word reading fluency measures.